An Evaluation of Hormone Levels in Behçet's Disease - Sema KARAKUŞ,; Aslı NAR,; Selami Koçak TOPRAK,; Figen ATALAY,; Osman İlhami ÖZCEBE3, (Archives of Rheumatology, 2012)
Objectives: This study aims to evaluate the basal serum levels of the hypophysial, thyroidal, adrenal, and gonadal hormones and the disease activity in patients with Behçet's disease (BD). Patients and methods: Forty-three patients (22 males, 21 females; mean age 34 years; range 21 to 46 years) were divided into the following four groups according to the disease activity and presence of ocular involvement: Active BD (n=27), inactive BD (n=16), those with ocular involvement (n=14), and those without ocular involvement (n=29). A group of 40 (18 male, 22 female) healthy subjects matched according to age and gender were used as the negative control group. A positive control group (two males and 14 females) consisted of 16 patients with systemic lupus erythematosus. Triiodothyronin, thyroxin, the thyroid-stimulating hormone, the folliclestimulating hormone, the luteinizing hormone, the growth hormone (GH), dihydroepiandrosterone sulphate (DHEAS), estradiol, testosterone, basal cortisol, prolactin (PRL), and the adrenocorticotropic hormone were evaluated in all subjects. Results: No clinically significant differences were found between the BD groups and negative control group in terms of the basal serum levels of the hypophysial, thyroidal, adrenal, and gonadal hormones. When the hormonal values were evaluated with regard to disease activity and ocular involvement, the BD patients with ocular involvement showed significantly higher PRL and GH values in both genders and significantly lower DHEAS levels in female patients. Conclusion: Despite being a vasculitis-related disease, we can conclude that BD has no major influence on the endocrine system. Also, further, large-scale studies are needed to evaluate the correlations between PRL, GH, and DHEAS values and ocular involvement.